2022
DOI: 10.2174/1574892816666211130170149
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Values of Autophagy-related Genes in Triple-negative Breast Cancer

Abstract: Background: Triple-negative breast cancer (TNBC) is a highly aggressive malignancy with poor prognosis. Therefore, it is imperative to develop new prognostic or therapeutic biomarkers for TNBC. Objective: To explore the prognostic and therapeutic values of autophagy-related genes (ARGs) in TNBC. Methods: Overall, 157 TNBC patients’ data were obtained from The Cancer Genome Atlas database, and the ARGs were acquired from the Human Autophagy Database. Differentially expressed ARGs (DEGs) between tumor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prognostic indicators such as tumor size and lymph node metastases are insufficient for personalized treatment of patients with early-stage breast cancer. 82 Therefore, it is essential to identify molecular biomarkers and verify their usefulness as targets in personalized treatments and as indicators of clinical efficacy although achieving this is difficult owing to the lack of therapeutic targets. 83 , 84 Nevertheless, the following targets hold promise for patients with TNBC: PARP, insulin-like growth factor binding protein, PD-L1, interleukin-8, and glucocorticoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic indicators such as tumor size and lymph node metastases are insufficient for personalized treatment of patients with early-stage breast cancer. 82 Therefore, it is essential to identify molecular biomarkers and verify their usefulness as targets in personalized treatments and as indicators of clinical efficacy although achieving this is difficult owing to the lack of therapeutic targets. 83 , 84 Nevertheless, the following targets hold promise for patients with TNBC: PARP, insulin-like growth factor binding protein, PD-L1, interleukin-8, and glucocorticoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Meanwhile, studies on the relationship between mTOR/p-mTOR expression and gastric cancer, breast cancer, colorectal cancer, nasopharyngeal carcinoma, and urinary system tumors have shown that mTOR or p-mTOR may be considered promising markers for predicting aggressiveness and prognosis of cancer. [33][34][35][36][37] In NSCLC, dysregulation of Akt/ mTOR signaling pathway activity is one of the primary factors of carcinogenesis. mTOR promotes tumorigenesis and progression through activation of the downstream eIF4 complexes.…”
Section: Introductionmentioning
confidence: 99%